ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN DIGITAL BERBASIS MONUMEN PERISTIWA SEJARAH DI KOTA PAYAKUMBUH DAN KABUPATEN LIMA PULUH KOTA UNTUK MEMBANGUN KESADARAN SEJARAH - Irwan, Khorina; Yefterson, Ridho Bayu (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research discusses the development of e-teaching materials based on historical event monuments in Payakumbuh City and Limapuluh Kota Regency as a historical learning resource to build historical awareness. This E-Teaching Material media contains material on the history of monuments in Payakumbuh City and Limapuluh Kota Regency. The purpose of this research is as a learning resource in the history learning process and to build students' historical awareness of the monuments in the city of Payakumbuh and the fifty city districts. The research method used in this research is a qualitative descriptive method where the researcher is the key instrument and data processing is descriptive. Data collection techniques in this research used observation and interviews. The results and discussion of this research are that students have low enthusiasm for learning history which is caused by the monotonous use of history learning media so that students need interesting and creative learning media so that they can attract students' interest in learning history. The media that is the solution in this research is E-Teaching Material media which is based on monuments of historical events in the city of Payakumbuh and fifty city districts. It is hoped that this e-teaching material can be a solution to problems related to students' low enthusiasm for learning, so that effective history learning will be created and can achieve history learning goals.